102 A novel approach to addressing fibromyalgia symptomatology in SLE. (April 2019) - Rogers, Jennifer L; Eudy, Amanda M; Criscione-Schreiber, Lisa G; Pisetsky, David S; Sun, Kai; Doss, Jayanth; Clowse, Megan EB
Abstract : Background: The physician global assessment (PGA) is a 3-point visual analog scale assessing lupus disease activity. We implemented a Type II PGA to assess what we have termed Type II SLE symptoms. Type II SLE symptoms encompass fatigue, widespread pain, depression, sleep and cognitive dysfunction, and differ from Type I SLE symptoms, such as nephritis and inflammatory arthritis, the classic manifestations of SLE inflammation. Methods: This was a cross sectional study of SLE patients (ACR 1997 or SLICC 2012 criteria). All patients completed Systemic Lupus Activity Questionnaire (SLAQ), Patient Health Questionnaire-9 (PHQ9), and 2016 ACR Fibromyalgia criteria. The authors recorded PGA, SLEDAI and Type II SLE therapy. Patients were divided into 4 groups based on lupus disease activity. Type I SLE group was defined as SLEDAI 6, clinical SLEDAI 4, or active nephritis. Type II SLE group was defined as meeting fibromyalgia criteria. Mixed SLE group met criteria for Type I and Type II SLE. Low activity group did not meet criteria for either Type I or Type II SLE. Differences across groups were analyzed by Fishers exact test and ANOVA. A step-wise linear regression analysis examined predictors of Type II SLE treatment. Results: The authors performed a Type II PGA on 197 patients (92% female, mean age 45.8) from July to November 2018. Type II PGA strongly correlated with patient reported fibromyalgia and depression symptoms. Type II PGA did not correlate with Type I PGA or SLEDAI. Type II PGA was significantly higher in the Type II SLE and mixed SLE groups. Type II symptoms were addressed (counseling or intervention) at 45% of visits. In a regression model predicting Type II management, factors associated with increased Type II treatment were Type II PGA (OR 2.37, CL: 1.37, 4.08) and fibromyalgia severity score (OR 1.41, CL: 1.15, 1.72). Type I PGA (OR 0.46; 95% CI: 0.24, 0.89) was associated with decreased Type II SLE management. Compared to a cohort of 212 SLE patient visits from January to May 2018, prior to implementing the Type II PGA score, the rate of documented Type II SLE management in the Type II SLE group increased from 53% to 89% (p=0.03). Conclusions: A PGA specifically addressing Type II SLE symptoms can be implemented in practice and correlates with patient reported Type II SLE symptoms. Scoring a Type II PGA encourages the physician to address these important SLE symptoms. Further work is needed to validate the scoring. Funding Source(s): None